ANALISIS AGLOMERASI DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PENDAPATAN REGIONAL DI KABUPATEN PADANG PARIAMAN TAHUN 2015-2019 - Yulistrinanda Alfiani; Yudi Antomi (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to determine the analysis of agglomeration and economic growth in regional income inequality in Padang Pariaman in 2015-2019 in the agriculture, industry and tourism sectors. This type of research is quantitative descriptive and data collection techniques with secondary data analysis. The results showed that inequality in agriculture, industry and tourism always increased. This can be seen in the tourism sector with an amount of -0.95 or -0.0095% in 2019 and 2015 with an amount of -0.69 or -0.0069%. In the agricultural sector with a total of -0.93 or -0.0093% and while the industrial sector with an amount of -0.90 or -0.009% from year 2015-2019. The results of economic growth in the agriculture, industry and tourism sectors experienced high growth. The highest amount in 2015, which was 5.73 or 0.005% and in 2019 decrease by an amount of -90,89 or -0,908%. The results of agglomeration in the agriculture, industry and tourism sectors, namely in the tourism sector in 2015 amounting to 0.31 or 0.003%, in 2019 decreased by an amount of 0.05 or 0.005%. In the agricultural sector has an amount of 0.07 or 0.007% and the industrial sector has an amount of 0.10 or 0.01% in 2015-2019.